The use of antidepressants and their long-term consequences in young people: An updated literature review (Research, Society and Development, 2023)
In recent decades, the use of antidepressant medications among adolescents has increased in many parts of the world. Therefore, it is important to understand the context in which its use occurs to develop actions that promote reasonable and safe use. To this end, an updated bibliographical search was carried out on the topic, searching the databases Scielo (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature in Health Sciences) and Google Scholar, for the inclusion criteria were considered complete articles in Portuguese and covering the period from (2018 to 2023). The exclusion criteria were studies that do not have an objective and clear methodology, use other languages ​​such as English and Spanish and are not suitable for a specific period of the last 5 years. The objective of this study is to carry out an updated literature review on the use of antidepressants in young people and the effects of their long-term use, highlighting the importance of pharmaceutical professionals in the treatment of depression in adolescents and young people. Through this bibliographic study, we sought to understand the importance of detailed assessment by pharmaceutical professionals in the treatment of depression, suicide and prolonged use of antidepressants by adolescents and young people, who are often limited by the conditions and perceptions of family members and management difficulties. It is concluded that pharmaceutical assistance must be provided from the beginning to the end of the treatment, and the measures taken must include study of the prescription, accompanied by a doctor, analysis of the appropriate medication, ideal administration, medication route and dosage.